2021
DOI: 10.1016/j.euros.2021.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Characteristics, Follow-up and Outcomes of Active Surveillance for Prostate Cancer According to Ethnicity in the GAP3 Global Consortium Database

Abstract: Take Home Message Risks of upgrading and disease progression were higher among African than among Caucasian men on active surveillance for prostate cancer. Transitioning to treatment without progression was highest among Asian men. Understanding of the reasons for these differences requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…79 However, stratifying by ethnicity among 9,158 patients in the GAP3 Global Consortium Database and 1,315 in the Canary Prostate Active Surveillance Study, no differences were observed in progression to treatment by ethnicity (White, African/Afro-Caribbean/black, or Asian). 80,81 Finally, Catalona and colleagues examined 7,279 patients who underwent germline genetic analysis and found no significant association between time to progression and genetic ancestry or self-reported race. 82 Overall, the preponderance of data suggests that race/ethnicity appears to account for a small proportion of variation in AS outcomes and should not be used as a selection criterion for AS.…”
Section: As Of Localized Pcamentioning
confidence: 99%
“…79 However, stratifying by ethnicity among 9,158 patients in the GAP3 Global Consortium Database and 1,315 in the Canary Prostate Active Surveillance Study, no differences were observed in progression to treatment by ethnicity (White, African/Afro-Caribbean/black, or Asian). 80,81 Finally, Catalona and colleagues examined 7,279 patients who underwent germline genetic analysis and found no significant association between time to progression and genetic ancestry or self-reported race. 82 Overall, the preponderance of data suggests that race/ethnicity appears to account for a small proportion of variation in AS outcomes and should not be used as a selection criterion for AS.…”
Section: As Of Localized Pcamentioning
confidence: 99%